(‐)‐Epigallocatechin‐3‐gallate and atorvastatin treatment down‐regulates liver fibrosis‐related genes in non‐alcoholic fatty liver disease. (3rd October 2017) - Ying, Le; Yan, Feng; Zhao, Yueling; Gao, Hugh; Williams, Bryan RG; Hu, Yiqun; Li, Xiaofang; Tian, Run; Xu, Ping; Wang, Yuefei
Summary: Non‐alcoholic fatty liver disease (NAFLD) and associated advanced liver diseases have become prevalent conditions in many countries and are associated with increased mortality. Gene expression profiles in NAFLD have been examined recently but changes in expression elicited by chemical compound treatments have not been investigated. Since (‐)‐Epigallocatechin‐3‐gallate (EGCG) and atorvastatin (ATST) exhibit similar efficacy in NAFLD models, we reasoned that some common key genes might alter after treatment of EGCG and ATST. Accordingly, we applied integrated bioinformatics analyses of RNA microarray data from EGCG and ATST treatment groups compared to controls in a NAFLD phenotypic mouse model. Using differential expression (DE) analysis, Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway analysis, Gene Set Enrichment Analysis (GSEA) and ClueGO enrichment, shared EGCG and ATST down‐regulated pathways were identified which included extracellular matrix (ECM)‐receptor interaction and protein processing in endoplasmic reticulum (ER). To refine key genes associated with liver fibrosis, a human NAFLD signature derived from patients of different fibrosis stages was analyzed. The results showed that fibrosis‐related genes Col1a1, Col1a2, Col3a1 and Col6a3 were significantly down‐regulated. These four genes were further validated as down‐regulated in an independent mouse NAFLD dataset. We conclude that EGCG and ATST treatment results in the significant down‐regulation of genes related to liver fibrosis.